Motion estimation of a flexible robotic manipulator with vibration and vision sensing - Luo, Xi (2017)
Compared to conventional rigid robotic manipulators and unlike traditional industrial robotic manipulators, flexible manipulator can be more efficient and safer to operate due to their low power consumption and lightness. Moreover, the next generation of robots will require compliance to be able to perform safe and close interactions with human beings. However, due to the flexibility in arms and joints, flexible manipulator control and operation suffers from severe structural vibration, leading to the inaccuracy in end-effector trajectory tracking and visual servoing.